Longer duration on a Chronic Disease Management plan is associated with long-term adherence to antihypertensive and antithrombotic medications following stroke - Ung, David; Kilkenny, Monique F; Olaiya, Muideen T; Kim, Joosup; Phan, Thanh; Cadilhac, Dominique A; Ma, Henry; Dewey, Helen M; Nelson, Mark R; Srikanth, Velandai K; Bladin, Christopher F; Fitzgerald, Sharyn M; et al. (International Journal of Population Data Science, 2020)
Introduction and Purpose Chronic Disease Management (CDM) plans are used by general practitioners to manage chronic diseases such as stroke. However, there is limited evidence that being on these plans improve adherence to secondary prevention medications after stroke. We aimed to assess the association of the duration on a CDM plan in improving adherence to secondary prevention medications following stroke. Methods Australian survivors of stroke or transient ischaemic attack were participants from the STAND FIRM trial. Patients were individually linked with claims for CDM plans from Medicare and dispensings of secondary prevention medications from the Pharmaceutical Benefits Scheme. We estimated (1) duration on a CDM plan based on the timing and Medicare items claimed and (2) the proportion of days that patients would have been covered by these medications (PDC), while accounting for deaths and instances of over-supply. Dosage for each quantity of medication was determined by the regularity in which patients returned for a refill. Logistic regression was used to evaluate factors associated with ≥80% adherence, up to 3 years after stroke, for each of antihypertensive, antithrombotic and lipid-modifying drugs. Results The median PDC for 563 patients (median age 70yrs; 36% female) ranged from 92% to 95% among the three classes of medications. Approximately 27% did not take up a CDM plan, 33% were on plans for <1.5 years and 40% for 1.5-3 years. Duration on a CDM plan (quintiles) was associated with adherence for antihypertensive (Odds Ratio (OR) 1.18, 95% confidence interval (95%CI) 1.00-1.40, p=0.029) and antithrombotic medications (OR 1.22, 95%CI 1.03-1.46, p=0.024), but not for lipid-lowering medications. Conclusion People on a CDM plan for longer had better adherence to antihypertensive and antithrombotic medications in the long-term after stroke. Use and ongoing reviews of CDM plans should be encouraged to improve adherence to secondary prevention medications after stroke.